31P magnetic resonance spectroscopy of the Sherpa heart: a phosphocreatine/adenosine triphosphate signature of metabolic defense against hypobaric hypoxia. - Hochachka, P W (1996)
Of all humans thus far studied, Sherpas are considered by many high-altitude biomedical scientists as most exquisitely adapted for life under continuous hypobaric hypoxia. However, little is known about how the heart is protected in hypoxia. Hypoxia defense mechanisms in the Sherpa heart were explored by in vivo, noninvasive 31P magnetic resonance spectroscopy. Six Sherpas were examined under two experimental conditions [normoxic (21% FiO2) and hypoxic (11% FiO2) and in two adaptational states--the acclimated state (on arrival at low-altitude study sites) and the deacclimating state (4 weeks of ongoing exposure to low altitude). Four lowland subjects were used for comparison. We found that the concentration ratios of phosphocreatine (PCr)/adenosine triphosphate (ATP) were maintained at steady-state normoxic values (0.96, SEM = 0.22) that were about half those found in normoxic lowlanders (1.76, SEM = 0.03) monitored the same way at the same time. These differences in heart energetic status between Sherpas and lowlanders compared under normoxic conditions remained highly significant (P < 0.02) even after 4 weeks of deacclimation at low altitudes. In Sherpas under acute hypoxia, the heart rate increased by 20 beats per min from resting values of about 70 beats per min, and the percent saturation of hemoglobin decreased to about 75%. However, these perturbations did not alter the PCr/ATP concentration ratios, which remained at about 50% of the values expected in healthy lowlanders. Because the creatine phosphokinase reaction functions close to equilibrium, these steady-state PCr/ATP ratios presumably coincided with about 3-fold higher free adenosine diphosphate (ADP) concentrations. Higher ADP concentrations (i.e., lower [PCr]/[ATP] ratios) were interpreted to correlate with the Km values for ADP-requiring kinases of glycolysis and to reflect elevated carbohydrate contributions to heart energy needs. This metabolic organization is postulated as advantageous in hypobaria because the ATP yield per O2 molecule is 25-60% higher with glucose than with free fatty acids (the usual fuels utilized in the human heart in postfasting conditions).